The Saga of Conflict Transformation and Peace Process in Nepal: A Unique Account - Adhikari, Debendra Prasad (Journal of Education and Research, 2017)
Transforming from conflict to a state of peace has been a global concern in the 21st century. Nepal involved in peace building process in a unique way. Nepal’s effort to solve armed conflict has proven to be a unique Nepali model in peace and conflict literature. This paper examines the context of armed conflict and the peace process in the light of managing combatants of the Communist Party of Nepal (Maoist) thereby contributing to the approach of transforming armed conflict into a state of global peace. For this purpose, I have used the meta-analysis to illuminate the situation of transformation from conflict to peace. Additionally, I have reflected on the ideas as a peace and human rights activist in Nepal. The paper concludes that the consensus among the conflicting parties to address the causes of armed conflict with their own ideas can uniquely contribute to conflict transformation and to establish negative peace. The reflection of this paper will pave the way for further research on peace education focusing on positive and negative peace in the post-conflict political context of the country.